Soft Matter Informatics: Current Progress and Challenges. Issue 1 (11th November 2018) - Peerless, James S.; Milliken, Nina J. B.; Oweida, Thomas J.; Manning, Matthew D.; Yingling, Yaroslava G.
Abstract: The number of applications of informatics or data‐driven discovery is growing in many fields, including materials science. The large amount of data that is readily available, combined with high‐level statistical algorithms, is proving to be extremely useful in developing complex predictive models with little to no human supervision or bias. However, in the field of soft matter, which includes complex materials such as polymers, liquids, emulsions, colloids, and gels, there is a slower adoption of informatics strategies than in adjacent fields. Here, the current state of soft matter informatics is discussed. Challenges specific to soft materials, including data classification, various degrees of organization at multiple length scales, and process‐dependent properties require unique approaches by researchers in order to develop robust informatics approaches in soft matter. The current ability to extract and analyze the information from the PoLyInfo database is demonstrated by the fitting of the Flory–Fox equation for glass transition temperature for several polymers. This Progress Report serves to introduce and excite the scientific community about the remarkable potential of informatics for exploring the properties of soft materials. Abstract : The specific challenges and potential of data‐driven informatics approaches in the field of soft matter are discussed in the context of similar approaches in other physical sciences. The current state of informatics in polymeric materials is explored via review and an open case study leveraging polymer data for theoretical model fitting.